Model for improving organizational and methodological aspects of management accounting of intangible assets and goodwill - Yasyshena, Valentyna; Pylyavets, Viktor (Herald of Economics, 2024)
Introduction. In the conditions of the rapid development of the informatization of the economy and the increased level of competition, there is a need to cover a wider range of objects of intangible origin in management accounting. This is due to the importance of intangible assets (hereinafter referred to as IA) and objects related to them, their growing influence on economic processes, which makes it necessary to improve the methodology and organization of their management accounting. The purpose of the article is the formation of a comprehensive model that will contribute to the improvement of the methodology and organization of management accounting of ІA and goodwill in the management accounting system. Research methods. Analysis and synthesis - for studying the object and subject of research; modeling - to determine the influence of factors on the methodology of management accounting of ІA, goodwill and the formation of a complex model; tabular – for presenting groups of analytical accounts of intellectual assets; abstract-logical - for the formation of theoretical generalizations and conclusions. Research results. The principles and classification features of management accounting of IA and objects related to them are outlined. The concepts of «intellectual capital» and «internal goodwill» have been clarified. The organizational principles of accounting and information provision of the management system of intangible assets have been formed. The analysis of the influence of factors (external, internal) on the functioning of food industry enterprises and the methodology of accounting for ІA and goodwill was carried out. The comprehensive model summarizes the main methodological and organizational directions for improving the management accounting of ІA and objects related to them for food industry enterprises. Prospects. It is advisable to focus further scientific research on the development of methods for evaluating intellectual assets. This will significantly affect the quality of the formation of the information component about the internal goodwill of the enterprise, the validity of management decisions for the effective use of these objects, and will also serve as a confirmation of the calculation of the value of the enterprise.